The role of chinese culture and strategic orientation in enhancing competitive advantage and firm performance in Indonesian chinese family companies - Susan Kustiwan; Asep Hermawan; Agustinus Sri Wahyudi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Chinese culture plays an important role in shaping the dynamics of family businesses in Indonesia, especially in the context of increasingly intense business competition. This study aims to address gaps in understanding the influence of Chinese culture, including guanxi culture, Confucian inheritance, and the succession process, as well as strategic orientation, namely entrepreneurial orientation and market orientation, on firm performance, with competitive advantage as a mediating variable. The research method used in this study is a quantitative method with a data analysis approach using Structural Equation Modeling (SEM). Data were collected through surveys distributed to 232 Chinese family businesses in Bekasi and DKI Jakarta. The sample was selected using a non-probability sampling technique with a purposive sampling approach, where companies were chosen based on certain criteria, such as family structure, years of operation, and family member involvement in management. The data collection instrument consisted of structured questionnaires containing questions about corporate culture, strategic orientation, competitive advantage, and firm performance. The results of the study show that competitive advantage significantly mediates the influence of the succession process, entrepreneurial orientation, and market orientation on firm performance. However, guanxi culture and Confucian inheritance do not show a significant influence on firm performance, either directly or through competitive advantage. These findings contribute theoretically with five novel models related to the relationship between Chinese culture, strategic orientation, and firm performance in Indonesia. The implications of this study suggest that Chinese family businesses need to focus more on innovation, market adaptability, and succession management to maintain competitiveness and enhance business performance, while traditional values such as guanxi and Confucianism may require further adaptation to remain relevant in the modern business context.